Cardiac Tamponade in a Chronic Renal Failure Patient with Suspicion of Dialysis Pericarditis: A Case Report - Wulandari, Pipiet; Suryono, Suryono; Prasetyo, Aris; Firdaus, Jauhar; Sofiana, Kristianingrum Dian; Indreswari, Laksmi; Handoko, Adelia; Setia, Bagus (Indonesian Journal Publisher, 2024)
Pericardial effusion is a condition characterized by fluid accumulation in the pericardial cavity. This fluid accumulation can cause disturbances in cardiac contractility, affecting hemodynamic stability. Fluid accumulation is caused by several factors, ranging from the amount of fluid, the speed of fluid accumulation, and the ability of the pericardium to accommodate fluid. One of the causes of pericardial effusion is pericarditis. Pericarditis can be caused by infection and non-infection, such as in patients with chronic renal failure with an incidence of 2-21%, which can lead to cardiac tamponade. In this study, a 46-year-old male patient who came to the emergency room of Dr. Soebandi Hospital, Jember with complaints of shortness of breath in the last 2 months. The patient also complained of heartburn. The patient had a history of chronic renal failure and routinely performed hemodialysis. On examination of vital signs, thoracic photographs, and echocardiography, a picture of cardiac tamponade was found. Cardiac tamponade can occur in patients with chronic renal failure. This is due to the condition of uremia which causes pericarditis. Inflammation of the pericardium causes blood that is intravascular to enter the pericardial cavity, causing fluid accumulation there. If not treated immediately, it can lead to cardiac tamponade which endangers the patient's life.